A budapesti bérlakásszektor privatizációjának társadalmi- és városszerkezeti hatásai - Kovács, Zoltán (Tér és Társadalom, 1992)
A common feature of the emerging East-European democracies is the introduction of market onomy. Although the social and economic development of these countries have had signifiant differences in the past, each of them considers privatization as the key element of the curent economic and social transformation. Beside the privatization of the productive sector, hich goes on rapidly now, great attention is paid to the privatization of housing, which influences the living conditions in a more direct way. The aim of this paper is to provide an verview about the development of housing in Budapest, with special attention to the most ecent phenomena and trends (i.e. privatization). In the case of Budapest, we can identify three major periods in the history of housing onstruction and the physical expansion of the city. The first dynamic phase of urban evelopment dates back in the lant decades of the 19th century, when the present urban structure s shaped. Due to the rapid growth of population, housing construction was dominated mainly by speculative builders during this period. As a consequence, a huge private rented sector merged in the inner part of the city, in the form of low-quality four- and five-storey tenement locks which housed mainly low-income and – to a lesser extent middle-class families. The next extensive phase of urban development can be identified with the inter-war period when the main path of city development shifted outwards, to the peripheral zone. Housing construction in this period remained at a fairly low standard and only a relatively small part of the city, mainly on the Buda side, was built according to the new architectural principles of the 1920s and 1930s. A great deal of residential segregation persisted, even within the rapidly expanding industrial suburbs where great barriers could be observed, between elite workers who were provided with flats in workers' colonies set up by large-scale firms, and the mass of immigrant proletarians. A radical shift came about in the housing policy at the end of the 1940s, as part of the socialist transformation of the country. Capitalist production and distribution of housing, which were blamed for the previous inequalities, was effectively abolished. Instead, the state became the dominant force in urban housing, owning most of the housing stock indirectly through the local authorities. The new rent system, the nationalization of housing and the constant state intervention into the allocation process were to abolish the old forms of social inequality according to the principal goal of the Stalinist regime. At the same time, housing construction and public infrastructure received very low priority in the economic plans of the 1950s, the growth of the publicly rented sectór could be attributed merely to nationalization at this time. Most of the property and dwellings of the old ruling class were confiscated by state and redistributed to members of the working class, party apparatus and armed forces. Due to excessive nationalization, the ratio of state sector rapidly grew up to 75 per cent within three years. Large-scale state housing construction could only take place after 1956, when housing became a significant element of the living-standard policy of the Kádár regime. The new housing policy was embodied in the Fifteen Year National Housing Development Plan, which projected the construction of 250.000 new dwellings in Budapest alone (one million in the country as a whole) between 1960-1975. The following years saw a rapid increase in state housing expenditure and construction, a dynamism almost comparable to that of the late 19th century. The share of state dwellings in new housing rose from 50-55 per cent to 70-72 per cent by the mid-1970s. As in the other state socialist countries, the housing industry in Hungary was based mainly on prefabricated technology and the newly established housing factories chumed out a vast number of almost identical, two-roomed flats on large housing estates from the late 1960s. Another important feature of this period, the one following the introduction of the New Economic Mechanism in 1968, was that a new housing policy was implemented which realized the role of the market and encouraged the private sector. The Fifteen Year National Housing Development Plan was eventually fulfilled, though only thanks to a 50 per cent overshoot in private construction. In Budapest, direct privatization of housing was negligible before 1982, and it remained at a very low level until 1988. Yet, we could observe the relative growth of the weight of the private sphere from the early 1960s. This could be attributed, on the one hand, to the general liberalization of the economy which included the housing sector too, and, on the other hand, to the gradual state withdrawal from housing construction especially beginning with the late 1970s. At the end of the 1970s, the economy and the living standards began to stagnate, while the inflation rate increased. Hungary entered the longest economic crisis in its modern history, and consequently state housing construction began to fall. In 1986, the state constructed 2.100 dwelling units in Budapest which was only 18 per cent of what it had been six years earlier. According to the latest information, only 100 new dwellings will be built by the state in 1991 in Budapest. As the large-scale state housing projects came to an end, most of the state-owned building companies also went bankrupt. Denationalization of state housing has been officially recognized and regulated in Hungary since 1969. The original decree of the government still operates and constitutes the legal basis for the present privatization. Despite the legal opportunity, Budapest city council had agreed to privatize only 2.200 dwelling units until 1982. Between 1982 and 1989, this figure slowly g rew and reached almost 16.000. Nevertheless, privatization could speed up only after 1989, when district councils became responsible for the local state housing stock again. Consequently, an additional 100 thousand state dwellings were designated for privatization in Budapest during the years 1989-1990. If the speed of privatization remains at this level, another 100 thousand state appartments will be desingnated for sale by the end of 1991. It means that the share of state-housing will be reduced to 25 per cent, and it is doubtfull at the moment, whether the process will stop at this point or will accellerate further. The scale of the privatization of state housing shows remarkable differences within Budapest. ror example, in the 2nd and 12th districts, more than half of the state housing stock had already been privatized by the end of 1990. These are the posh areas of Budapest with the highest prices per square meter. On the other hand, the pace of privatization remained quite modest (less han 10 per cent) in the traditional working-class areas such as Újpest, Kőbánya or Csepel. In fact, local governments privatize state housing at extremely low prices. According to the law, a public flat can be sold to its renter for 15 per cent of the flat's market value if it has not been restored in the last 15 years. However, the new owner does not have to pay the total rrice in one sum, but only 10 per cent of it. The remaining part of the price can paid in monthly instalments over a maximum period of 35 years. Since the overwhelming majority of the council flats in Budapest have not been renovated during the last 15 years, most of the flats are being rivatized according to these soft criteria. If the appartment has gone through renovation within the last 15 years, the price is going to be 30 per cent of the current market price. However, given the lack of accurate information we found that local governments are not aware of real market prices and they calculate the appartment prices 10-20 per cent below the real value. Moreover, if the renter pays the oalculated amount in one sum, he can get 40 per cent discount from the original price. It means tlat one can buy a flat in Budapest for 11 per cent of its market value. We can easily understand, that the higher the values of the flat, the bigger profit can be made. Indeed, the wealthiest strata of the society, those who occupy the most expensive areas of the city (i.e. 2nd and 12th districts) were the first to realise this, thus the level of privatization is nost advanced in these districts. It can be anticipated that social housing will shortly disappear in these parts of Budapest. Obviously, this kind of privatization is very irritating for those who have not had access to state housing in the past. Since most of them are lower class people they feel that the same people are privileged by the new regime who were privileged by the old one, and enjoyed free accomodation as a "state gift" earlier. Privatization at this price means a second gift, an undeserved subsidy for them again. Local governments are in a difficult situation. The Budapest city council and the local district councils are ruled by liberals who are in opposition in the Parliament. The centre-right conservative government cut public expenditure, and left local authorities without any central subsidy. Therefore there is a great demand at local governments to make money by means of privatization.